Ernest scared stupid - Cherry, John (John R.); Varney, Jim.; Byrge, Bill.; Cadenhead, John.; Nagler, Austin; Gale, Charlie; Sams, Coke.; Touchstone Pictures; Touchwood Pacific Partners I.; Touchstone Home Video (Firm); Buena Vista Home Video (Firm) (Burbank, Calif. : Touchstone Home Video : Distributed by Buena Vista Home Video, 2002)
Ernest P. Worrell accidentally unleashes an evil demon from its sacred tomb--causing the awakened foe to go on a devastating rampage. Ernest desperately attempts to prevent the town's destruction, but is scared stupid by a 200-year old curse.
Director, John Cherry; producer, Stacy Williams; screenplay, story, John Cherry, Coke Sams.
Jim Varney, Bill Byrge, John Cadenhead, Austin Nagler.
DVD, full screen presentation; Dolby Digital surround sound.
Closed captioned for the hearing impaired.
107481
Keywords: Trolls -- Drama; Closed caption video recordings; Feature films; Comedy films; Slapstick comedies; Horror films and programs; Video recordings for the hearing impaired